MEMPROMOSIKAN PERUMPAMAAN DALAM MENGAJAR AGAMA KATOLIK - Agustinus Wisnu Dewantara (Bahasa Indonesia, 2018)
Jesús preached the kingdom of God. Many of his parables begin: The kingdom of God is like….” But what exactly is the kingdom of God? Parables are enigmatic stories. Metaphorically they are set beside the idea of a kingdom of God, but idea the idea of kingdom is itself mysterious. Everyone who hangs around churches has heard of the parables of Jesus. They are familiar. They have been allegorized, psychologized, and sometimes reduced to pointed “lessons” on moral behavior. But mysteriously, after twenty centuries they still generate retelling and still are puzzling. Maybe the today teacher who preach must be converted. The today teacher cannot preach about the kingdom of God as if it were something somewhere out in the world beyond us. Remember, the kingdom of God is a happening, and people live within its happening. Instead we (and many teacher today) must speak the kingdom of God (and also religion preaching) happening all around us.